Discrepancy evaluation of social reconstruction-based curriculum implementation at Sekolah Rimba Indonesia - Rika Yustikarini (Curricula: Journal of Curriculum Development, 2023)
This study aims to determine the suitability of implementing a social reconstruction-based curriculum at Sekolah Rimba Indonesia based on the ideological criteria and characteristics of the social reconstruction curriculum of experts, namely John D., Mc Neil, and Michael Stephen Schiro used the discrepancy evaluation model. The selected resource persons are teachers and principals at Sekolah Rimba. This data collection technique is through interviews, observations, and document studies. The data analysis technique used Miles and Hubberman, namely condensation and presentation of data, and conclusion. The results of the study describe the implementation of a social reconstruction-based curriculum at Sekolah Rimba Indonesia, which includes aspects of the basic concepts and objectives of the social reconstruction curriculum, teaching perspectives, the nature of learning, teaching, and evaluation have been following the criteria set at the beginning of the study. The implementation of the curriculum at Sekolah Rimba Indonesia can be maintained and used as a reference for schools that adopt the social reconstruction curriculum. In this study, the long-term outcomes assessment aspect of Sekolah Rimba Indonesia was not included as an aspect of the research.   Abstrak Penelitian ini bertujuan untuk mengetahui kesesuaian antara implementasi kurikulum berbasis rekonstruksi sosial di Sekolah Rimba Indonesia yang berdasarkan dengan kriteria Ideologis dan ciri khas kurikulum rekonstruksi sosial para ahli yaitu John D., Mc Neil dan Michael Stephen Schiro dengan model evaluasi discrepancy. Narasumber yang dipilih yaitu guru dan kepala sekolah di Sekolah Rimba. Teknik pengumpulan data ini melalui wawancara, observasi, dan studi dokumen. Teknik analisis data menggunakan Miles dan Hubberman yaitu kondensasi dan penyajian data, serta penarikan kesimpulan. Hasil penelitian menggambarkan implementasi kurikulum berbasis rekonstruksi sosial di Sekolah Rimba Indonesia yang meliputi aspek konsep dasar dan tujuan kurikulum rekonstruksi sosial, perspektif pengajaran, sifat pembelajaran, pengajaran, dan evaluasi telah sesuai dengan kriteria yang ditetapkan di awal penelitian. Implementasi kurikulum di sekolah Rimba Indonesia dapat dipertahankan dan dijadikan rujukan sekolah yang mengadaptasi kurikulum rekonstruksi sosial. Dalam penelitian ini aspek penilaian long term outcomes Sekolah Rimba Indonesia tidak dimasukkan sebagai aspek penelitian. Kata Kunci: implementasi kurikulum; kurikulum rekonstruksi sosial; model evaluasi discrepancy